TRANSFORMATION TYPOLOGY OF ARABIC MEANINGS (Contextual Semantic Study of the Language of Sex in The Hadith) - Muhandis Azzuhri; Muslich Shabir; Athoillah Islamy (ALSINATUNA, 2021)
This research aims to reveal typology of transformation of the Arabic meanings to the language of sex in the hadith. Such transformation of the meaning had developed dynamically and inconstantly from time to time (diachronic) due to the underlying context. This library research utilizes contextual semantic theory with language and historical approaches. The results show that the transformation of the meaning of sex language in the hadiths was influenced by several factors. First, historical, social and cultural contexts. There were several sexual behaviors in the prophetic era which were considered deviant (sexual deviation) because they were not in accordance with Arab social culture at that time, that was doggy style narrated by يجبّون and حوَّلتُ رحلي اللَّيلةَ structures, not missionary style جَلَسَ بَيْنَ شُعَبِهَا اَلْأرْبع. Second, emotive and psychological context by refining a word النيك / intercourse which later was translated into بُضْعُ / goods, يفضى/ irrigating, يلمس / touching. Third, linguistic context, it is not idiomatic, such as a word خاتم / sealing, which can change the the compilation meaning when the word is structured with other word as in the hadith لا تفتح الخاتم إلا بحقه. The word is a metaphor meaning of the 'virginity' term. Fourth, context of situations and conditions (Siyāq Mauqif-Hāl). This context explains that the ‘sex term’ can transform in meaning because it was conveyed in different situations and conditions with the euphemism and kināyah (metaphor) expressions, such asالنيك, الجماع, يجبون, الغيلة, سحاق, حولت رحلي البارحةand فتح الخاتم إلا بحقه.